Aging in Place on a Hiperlocal Level. The Role of Grassroots Initiatives in the American Landscape of Eldercare Services on Example of the Village Model of Care - Zapędowska-Kling, Kaja Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
“Aging in community” is a well‑known concept promoted by policy‑makers, researchers and practitioners in the field of social policy, social gerontology and social work as an alternative for institutionalized, residential forms of care. It focuses on the ability of elderly people to stay at their own households, communities, neighborhoods and environments as long as possible, with the simultaneous provision of care directly at home. It provides the sense of security and subjective well‑being to elderly people, who often simultaneously experience loneliness and limited independence. The article aims at presenting and discussing an innovative case of the American village model of care, which corresponds with and fits in the concept of “aging in place” and plays complementary role to the publicly‑funded provision of care. The paper analyzes main assumptions of the village model of care, offers critical assessment of its weaknesses and strengths and provokes further discussion on potential adaptability of the village model in Polish context.